ASSESSMENT OF RELIABILITY OF THE CITY PUBLIC TRANSPORT FUNCTIONING IN THE RUSSIAN FEDERATION CITIES - M. I. Sharov; A. Yu. Mikhaylov (Вестник СибАДИ)
Introduction. The paper deals with the results of the reliability of urban public passenger transport routes. One of the main objectives is to consider the indicators for assessing the reliability of the urban passenger transport system, which have not yet been used in Russian practice. The peculiarity of these indicators is that the initial information can be obtained on the basis of modern bus equipment (GLONASS/GPS). The possibility of using these indicators, as well as the development of scales of reliability levels at the moment is an important scientific problem.Materials and methods. The authors proposed modern indicators for assessing the reliability of urban passenger transport routes, such as the time index and the associated buffer time indicator. The authors used the methods of mathematical statistics to process the data on the duration of bus traffic.Results. The authors obtained the reliability characteristics of urban passenger routes. Moreover, the paper presented the comparison of the reliability values on the example of Irkutsk and Angarsk.Discussion and conclusions. The authors reveal the range of values of the time and buffer indices based on the data of route networks of two different cities. Therefore, the authors offer the estimation scale of the reliability levels on routes.